During analysis, language rules are applied to the parsed text. This involves comparing each word against a dictionary or a set of predefined language rules to determine if it is spelled correctly - Dina Aprilia; Septi Yovi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to investigate the critical role of an analysis stage in detecting spelling errors in news texts. Spelling errors in news text can hinder understanding and reduce the credibility of the information. The analysis stage in this research includes identifying spelling error patterns, selecting effective analysis methods, and developing a spelling error detection algorithm. Through this approach, this research aims to improve the quality of news texts by reducing the number of spelling errors that may occur. The research method involves analyzing news texts that have been identified as potential sources of spelling errors. It is hoped that the research results will provide valuable insights into the development of automatic systems to detect and correct spelling errors in news texts, thereby increasing the accuracy and credibility of information conveyed through this media